Fiber optic salinity sensor using beam-through technique - Rahman, H.A.; Harun, Sulaiman Wadi; Yasin, M.; Ahmad, Harith (Elsevier, 2013)
A fiber optic displacement sensor is proposed to sense salinity based on different concentration of sodium chloride (NaCl) in de-ionized water using the beam-through technique. The performance of a 594 nm and 633 nm He–Ne laser as the light source are compared. For a concentration change of sodium chloride from 0 to 12% in de-ionized water, the output voltage increase linearly and the sensitivity is dependent on the displacement position of the receiving fiber from the quartz cell containing the sodium chloride solutions. Measurements taken at higher displacement positions contribute to lower sensitivity with the highest sensitivity of 0.0237 mV/% and 0.0412 mV/% occurring at the 0 mm displacement position for the 594 nm and 633 nm He–Ne lasers, respectively. Furthermore, a better limit of detection of 1.44% is achieved when the 633 nm He–Ne laser is used compared to the 1.28% limit of detection achieved by using the 594 nm He–Ne laser. The main novelty of this sensor is that it is contactless and non-destructive which are attractive features for applications involving delicate and hazardous processes.